2021
DOI: 10.26803/ijlter.20.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian University Students’ Attitudes toward Online Learning during the COVID-19 Pandemic and Lockdowns: Obstacles and Solutions

Abstract: This study aimed to investigate Jordanian university students’ attitudes toward online learning during the COVID-19 pandemic and lockdowns, shed light on the obstacles students encounter in online learning, and suggest possible solutions. A questionnaire designed by the researchers was used to elicit responses from a study sample consisting of 195 students from the Department of English Language and Literature at the University of Jordan – Aqaba. As this is an attitudinal study, the survey questionnaire was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
8
3
Order By: Relevance
“…Similarly, the results in the Köprülü and Öznacar study (2019) carried out in Turkey regarding the attitudes of university students towards distance learning in foreign language education report statistically significant differences in attitudes along the gender divide, with female students' attitudes towards distance learning being more positive compared to the male students' ones. On the other hand, other studies reported no gender differences in impacting learners' attitudes (Mahfouz & Salam, 2021). Based on the results from our study we cannot entirely reject RH1, which can be accepted merely regarding general attitudes to distance learning.…”
Section: Discussioncontrasting
confidence: 86%
“…Similarly, the results in the Köprülü and Öznacar study (2019) carried out in Turkey regarding the attitudes of university students towards distance learning in foreign language education report statistically significant differences in attitudes along the gender divide, with female students' attitudes towards distance learning being more positive compared to the male students' ones. On the other hand, other studies reported no gender differences in impacting learners' attitudes (Mahfouz & Salam, 2021). Based on the results from our study we cannot entirely reject RH1, which can be accepted merely regarding general attitudes to distance learning.…”
Section: Discussioncontrasting
confidence: 86%
“…This has made the 60% of the students agree to join English online learning process. However, as learning online is basically quite complicated and adaptation to it needs time, there are obstacles present (Mahyoob, 2020;Mahfouz & Salam, 2021;Lassoued, Alhendawi & Bashitialshaaer, 2020). Many obstacles are obvious during an online learning process, especially in the aspects of needed facilities and internet connection.…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, the digital mode of education was not accepted by the students as a substitution for conventional education amid the coronavirus pandemic (Mahajan, 2020). According to Mahfouz and Salam (2021), most higher education students like the traditional way of education rather than online classes because the conventional mode engages learners directly with mentors whereas in digital education this aspect is much weaker. During COVID-19 the majority of tertiary learners were reluctant to take online classes (Abbasi et al, 2020;Male et al, 2020).…”
Section: 3mentioning
confidence: 99%